2009
DOI: 10.1245/s10434-009-0854-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile Prospectively Predicts Peritoneal Relapse After Curative Surgery of Gastric Cancer

Abstract: Gene expression profile inherent to primary gastric cancer tissues can be useful in prospective prediction of peritoneal relapse after curative surgery, potentially allowing individualized postoperative management to improve the prognosis of patients with advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…In many less developed countries, however, GC is mostly detected only in its advanced stages, precluding curative surgical resection and necessitating systematic treatment. The low efficacy of current therapies results in advanced or metastatic GC having a low survival rate of 5–20%, and a particularly poor prognosis for peritoneal GC recurrence [5, 6]. Together, these facts thus reinforce the urgent need for improved biomarker-driven, “targeted” therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In many less developed countries, however, GC is mostly detected only in its advanced stages, precluding curative surgical resection and necessitating systematic treatment. The low efficacy of current therapies results in advanced or metastatic GC having a low survival rate of 5–20%, and a particularly poor prognosis for peritoneal GC recurrence [5, 6]. Together, these facts thus reinforce the urgent need for improved biomarker-driven, “targeted” therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The search for reliable tumor markers and consistent prognostic indicators has proven difficult. Several authors have attempted to predict GC disease and prognosis based on single or multiple genes [3-8], but there are discrepancies between the studies, and currently no gene signature or biomarkers are in routine clinical use. Understanding the mechanisms underlying gastric cancer is one of the major challenges in cancer genomics.…”
Section: Introductionmentioning
confidence: 99%
“…Next, to further support the association between PTX3 expression and metastatic potential in gastric cancer, PTX3 gene expression profiles from a cohort of 108 gastric cancer tissues associated or not associated with peritoneal relapse (GSE15081) were analyzed. Peritoneal relapse is one of the most common features of tumor progression associated with advanced gastric cancer [34]. Gene expression data from these patients with gastric cancer demonstrated that relapsed gastric cancer tissues expressed higher levels of PTX3 than relapse-free tissues (Figure 2B, P <0.005), indicating an increase in PTX3 expression in relapsed gastric cancer, despite a lower level of PTX3 expression in primary gastric cancer than in nonmalignant tissues.…”
Section: Resultsmentioning
confidence: 97%
“…Bone-metastasized tumor cells compete with HSCs to occupy the osteoblastic niche during the process of bone-associated metastasis [6, 7, 34, 38]. We next hypothesized that elevated PTX3 expression in bone metastatic HTB135 cells stimulates the interaction of bone metastatic gastric cancer cells with OBs.…”
Section: Resultsmentioning
confidence: 99%